1996
DOI: 10.1007/bf01708096
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction for patients with cirrhosis of the liver in a medical ICU: A comparison of the APACHE scores and liver-specific scoringsystems

Abstract: To predict the outcome for patients with decompensated cirrhosis of the liver admitted to a medical ICU liver failure alone is not decisive. Liver-specific scoring systems (Mayo Risk Score, CCLI) are adequate, but the APACHE II and III proved to be more powerful, because they include additional physiologic parameters and therefore also take into account additional complications associated with this liver disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 16 publications
3
43
2
Order By: Relevance
“…less sick patients. Indeed, although APACHE II works well for severely ill cirrhotic patients admitted to ICUs (13,17,29,(36)(37)(38), this is not the case when its predictive value is assessed in a population of cirrhotic patients with mortality rate of only 11.5% (41). Thus, our results are somewhat surprising, because the mortality rate in our sample was only 9.7% and nevertheless the scores showed an excellent performance.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…less sick patients. Indeed, although APACHE II works well for severely ill cirrhotic patients admitted to ICUs (13,17,29,(36)(37)(38), this is not the case when its predictive value is assessed in a population of cirrhotic patients with mortality rate of only 11.5% (41). Thus, our results are somewhat surprising, because the mortality rate in our sample was only 9.7% and nevertheless the scores showed an excellent performance.…”
Section: Discussionmentioning
confidence: 58%
“…These findings support the importance of evaluating the performance of a predictive model not only in terms of its discriminative capacity but also its calibration. If, as in some studies (13,17,36,38), we had based the evaluation on discriminative ability alone, we would say that the SAPS II and CPT scores had the best performance. Nevertheless, we found that the best calibration results were obtained by the SOFA and MELD scores.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Limitations of this scoring system for deciding timings of liver transplantation include limited discriminative ability, variability in measurement of clinical and laboratory determinants [7] of this scoring system and, importantly, limited ability to predict short-term mortality. Several other scoring systems have been described that attempt to evaluate prognosis of patients with cirrhosis of liver (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19]. However, none of these are applied widely in clinical practice because of their limited predictive ability and unacceptable complexity.…”
Section: Introductionmentioning
confidence: 99%
“…When critically ill patients with clearly de®ned problems, such as obstetric patients [18] and trauma victims [19], are studied, the discriminatory power of prognostic equations appears good. However, if the critically ill patients have complex multisystem disease, for example patients with hepatic cirrhosis [20] or sepsis [21], then the model's ability to assimilate the complex interactions between a combination of physiological abnormalities is not so good and the discriminatory power declines. When the clinical picture is complex, more¯exible systems, for example a neural network, may offer better performance [22].…”
Section: Discussionmentioning
confidence: 99%